2009
DOI: 10.1007/s00127-009-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical correlations, comorbidities, and suicidal tendencies in pathological Korean gamblers: results from the Korean Epidemiologic Catchment Area Study

Abstract: Pathological/problem gambling is highly associated with substance abuse, mood and anxiety disorders, and suicidality, suggesting that clinicians should carefully evaluate and treat such psychiatric disorders in gamblers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 32 publications
2
43
4
Order By: Relevance
“…Furthermore, those who do seek treatment are often driven to do so by psychological distress, disability, depressive disorder, or behavior that is characterized by addiction. Thus, their psychiatric co-morbidities may be greater than those of gamblers who do not ask for help (12). Pathological gamblers often suffer adverse consequences.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, those who do seek treatment are often driven to do so by psychological distress, disability, depressive disorder, or behavior that is characterized by addiction. Thus, their psychiatric co-morbidities may be greater than those of gamblers who do not ask for help (12). Pathological gamblers often suffer adverse consequences.…”
Section: Contextmentioning
confidence: 99%
“…The OR was no longer statistically significant when psychiatric disorders were factored in. It was concluded that gambling disorder is an independent risk factor for suicide (12).…”
Section: Gambling Disorder and Suicidalitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the statistics, the numbers of help-seeker coming to Community Centers on Gambling Problem in women has increased over 5 times from 37 in 2009 to 191 in 2013 [9], although the number of women seeking help consistently low compared to the estimated number of women problem gamblers. Due to a strong stigma attached to problem gambling, women problem gamblers might be reluctant to seek help even though they experience the negative consequences of gambling in Korea [10]. Therefore, there are many women problem gamblers who are in need of, and would benefit from receiving professional help.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors, however, believe that this is a defence strategy initially [10]. That's why anxiety and mood disorders are often described among gambling addicts [13]. These disorders are often described among mariners too.…”
mentioning
confidence: 99%